2018
DOI: 10.1177/1069072718816514
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance of the Career Futures Inventory–Revised Across General and Client Samples

Abstract: Establishing measurement invariance has been emphasized as an important scale validation procedure for group comparisons. The 28-item Career Futures Inventory–Revised (CFI-R) is a widely used measure of career adaptability that has demonstrated initial validity with various samples. The purpose of the present study is to further examine the validity of the CFI-R by testing measurement invariance between a general university student sample and a client sample. First, a five-factor confirmatory factor analysis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Previous research has found initial support for the validity of the CFI-R (Creed & Hood, 2015;Park et al, 2019;Rottinghaus et al, 2012Rottinghaus et al, , 2017. In the validation study of Rottinghaus et al (2012) for the CFI-R, Cronbach's alpha internal consistency estimates ranged from 0.78 to 0.90 and CFI-R subscales were moderately correlated.…”
Section: Type Of Employmentmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous research has found initial support for the validity of the CFI-R (Creed & Hood, 2015;Park et al, 2019;Rottinghaus et al, 2012Rottinghaus et al, , 2017. In the validation study of Rottinghaus et al (2012) for the CFI-R, Cronbach's alpha internal consistency estimates ranged from 0.78 to 0.90 and CFI-R subscales were moderately correlated.…”
Section: Type Of Employmentmentioning
confidence: 92%
“…Previous research has found initial support for the validity of the CFI‐R (Creed & Hood, 2015; Park et al., 2019; Rottinghaus et al., 2012, 2017). In the validation study of Rottinghaus et al.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research has focused on measurement invariance with specific career measures has included the Career Decision-Making Difficulties Questionnaire (e.g., Levin et al, 2020), the Career Satisfaction Scale (e.g., Spurk et al, 2015), Career Futures Inventory-Revised (e.g., Park et al, 2019), and the Career Indecision Profile (e.g., Abrams et al, 2013; Xu, 2020). These studies have primarily focused on determining measurement invariance across nonclinical and clinical samples, university students, and working adults, but have not examined veterans and civilians.…”
Section: Veterans’ Career Developmentmentioning
confidence: 99%
“…Measurement invariance of career assessments has been examined across different groups, including clinical samples (e.g., Park et al, 2019), country, age, gender, and decision status (Levin et al, 2020), and occupations (e.g., Spurk, et al, 2015). Military background, however, has not been the focus of many measurement invariance studies involving career measures.…”
Section: Introductionmentioning
confidence: 99%